Seek Singapore : stop the eye epidemic in kids - Ong, Evonne Hui Hoon (2015)
This paper presents “Seek Singapore: Stop the Eye Epidemic in Kids”, a health communication campaign, initiated by four final year students from the Wee Kim Wee School of Communication and Information at Nanyang Technological University (NTU). Targeted at parents with children below the age of seven, “Seek Singapore” aimed to reduce the incidence of childhood myopia at an early age by educating parents of the risks and long-term consequences of childhood myopia and hence informing and empowering parents to bring their children outdoors regularly to fight childhood myopia. This paper first summarises the primary and secondary research which helped shape the campaign. Based on the research findings, key messages, the big idea of “Visualising Myopia” which formed the backbone of the campaign’s branding, creative tactics and campaign strategies of “education”, “engagement” and “empowerment” were conceived. Both online and offline platforms were utilised in tandem in order to extend the campaign’s reach to large numbers of the target audience. This paper then documents the evaluation process of the overall effectiveness of the campaign tactics and strategies through a post-campaign survey, media monitoring, and assessment of target audience engagement on online and offline platforms. Finally, key achievements and limitations of the campaign were discussed, followed by future recommendations for subsequent campaigns pertaining specifically to children’s eye health. Original documents, campaign collateral, event photographs and relevant diagrams and tables can also be found in the appendices.